Resmin sinemaya yansımaları - Aksoy, Asiye (My University, 2024)
Bu çalışmanın amacı empresyonizm, sürrealizm ve Amerikan Realizmi akımlarının sinemaya nasıl etki ettiğini irdelemektir. Bu üç akımı incelemek için biri akımların özelliklerini taşıyan ve kendi sektöründe öncü nitelikte bir film ile biri modern sinemada bu akımların etkisini tartışacak bir film olmak üzere, her akım için iki film seçilmiştir. Empresyonizm için Jean Renoir ile Sophia Coppola’nın bir filmi, sürrealizm için Luis Bunuel ve David Lynch, Amerikan Realizmi için de Alfred Hitchcock ve Wim Wenders seçilmişlerdir. Modern Türkiye sinemasından da Nuri Bilge Ceylan’ın Kış Uykusu filminde realizm etkisi tartışılmıştır. Seçilen filmler kendi dillerini oluşturmuş auteur yönetmenlerin çalışmalarındandır. Sanat tarihinde bir akımın nasıl yeni bir akımı ortaya çıkarabildiği ve fotoğrafın icadının resme ve sinemaya ne gibi etkileri olduğu irdelenmiştir.

The purpose of this study is to evaluate how impressionism, surrealism and American realism influenced cinema. To examine these three movements, two films have been selected for each movement—one representing the characteristics of the movements and serving as a pioneering film in its industry, and the other discussing the influence of these movements in modern cinema. For Impressionism, films by Jean Renoir and Sophia Coppola have been chosen; for Surrealism, films by Luis Bunuel and David Lynch; and for American Realism, films by Alfred Hitchcock and Wim Wenders. Nuri Bilge Ceylan's film Winter Sleep from modern Turkish cinema has also been discussed for its influence of realism. The selected films are from the works of auteur directors who have created their own language in the art of filmmaking. The study explores how one movement in art history can give rise to a new movement and examines the impact of the invention of photography on painting and cinema. Key Words: impressionism, surrealism, realism
Keywords: Amerikan realizmi impressionism; empresyonizm; Motion pictures; realism; Sinema; surrealism; sürrealizm